Burkholderia gladioli strain NGJ1 deploys a prophage tail-like protein for mycophagy - Rahul Kumar; Sunil Kumar Yadav; Durga Madhab Swain; Gopaljee Jha (Microbial Cell)
Fungal pathogens are responsible for approximately two third of the infectious plant diseases. Historically they have been associated with several devastating famines, causing death and disabilities in humans. Mostly fungal diseases are being controlled by using fungicides which otherwise have adverse side effects on the health of consumers as well as environment. Due to extensive usages, pathogens have evolved resistance against most of the commonly used fungicides and rendered them ineffective. Controlling fungal disease in a sustainable and eco-friendly fashion remains a challenge. The antifungal biocontrol agents are being considered as potent, alternative and ecofriendly approach to manage fungal diseases. In our recent work, we have identified a rice associated bacterium; Burkholderia gladioli strain NGJ1 which demonstrates broad spectrum fungal eating (mycophagous) property. We determined that the bacterium utilizes its type III secretion system (Injectisome) machinery to deploy a prophage tail-like protein (Bg_9562) into fungal cells to devour them. The purified Bg_9562 protein from over-expressing recombinant E. coli strain demonstrates broad spectrum antifungal activity. Overall our study opens up a new opportunity to exploit prophage tail-like protein as potent antifungal compound to control plant as well as animal fungal diseases.